The Influence of Transformational Leadership and Intrinsic Motivation on Employee Performance with Discipline as An Intervening Variable - Asih Kurnianingsih; Lona Noviani; Rohaelis Nuraisiah; Jeffry Adriansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study is aimed to analyze the influence Transformational Leadership, intrinsic motivation on Job performance of employee, with work discipline as intervening variable. Case study at PT. Indonesia Pos Chemtech Chosun Ref. The population that used in this research is 45 (forty five) employees, from production department and Logistic department. This study used regression analysis to see the contribution from each independent variable Job Performance. Data analysis with multiple regressions and support by SPSS software (Statistical Package for Social Science) version 21.0. The result indicate that Transformational Leadership and Intrinsic Motivation has significant influence to job performance through work discipline as intervening mediator. The suggested variables are: transactional leadership, extrinsic motivation, job satisfaction and work environment. Because with more good performance of employees will also have a good effect on the company.